2018
DOI: 10.1016/j.jpainsymman.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Needs and Perception of Quality of Care and Satisfaction With Care in Hematology/Medical Oncology Patients: A Multicultural Assessment

Abstract: Spiritual needs are common in an ethnically, religiously, and linguistically diverse cancer patient population but may differ by cultural background. High levels of spiritual need are associated with lower levels of satisfaction and diminished perception of quality of care. Training clinicians to address patients' spiritual concerns, with attention to cultural differences, may improve patients' experiences of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 36 publications
1
67
0
8
Order By: Relevance
“…[36][37][38][39] Patients may also experience losses related to roles, identity and fear of death. 40 This focus on needs or challenges may be incomplete. Spiritual strengths have been identified as a potential resource during stressful life events 41 and cancer patients may use positive religious coping.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] Patients may also experience losses related to roles, identity and fear of death. 40 This focus on needs or challenges may be incomplete. Spiritual strengths have been identified as a potential resource during stressful life events 41 and cancer patients may use positive religious coping.…”
Section: Introductionmentioning
confidence: 99%
“…It can be asserted that, regardless of the participants' type of cancer, culture, religion, or ethnic group, spirituality positively enhances participants' psychological adjustment to their cancer. [33] Although the role of nurses in this area of patient spirituality is limited, they can provide basic spiritual information to facilitate the practice of religious rituals or provide contacts with religious mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in various settings and languages reported similar findings. [17][18][19] In Astrow and colleagues' 17 work with 727 patients with differing ethnicities, languages, and religions in four outpatient settings, most patients reported at least one spiritual need. Needing help with finding hope, prayer, or meditation, meaning in the illness experience, and relationship with God or other were the most frequently cited needs.…”
Section: Literature Reviewmentioning
confidence: 99%